Project Based Learning Improves Creative Thinking in Elementary Science Students: Pembelajaran Berbasis Proyek Meningkatkan Pemikiran Kreatif pada Siswa Sekolah Dasar Mata Pelajaran Sains - Salsabilla Octavia Putri; Vanda Rezania (Academia Open, 2025)
General Background: Creative thinking is a crucial competency in 21st-century education, particularly in elementary science learning where students are expected to explore real-world phenomena through inquiry and problem solving. Specific Background: Project Based Learning (PBL) is a student-centered approach that engages learners in designing and completing projects to construct knowledge actively. Knowledge Gap: Despite growing adoption, empirical evidence on students’ creative thinking development through PBL in Indonesian elementary science classrooms with small-scale experimental designs remains limited. Aims: This study aimed to examine the change in fourth-grade students’ creative thinking skills after participating in science learning using a Project Based Learning model. Results: Using a quantitative pre-experimental one-group pretest–posttest design with 13 students, data from eight essay tests showed normally distributed scores and a significant difference between pretest and posttest results (paired sample t-test, sig. 0.000 < 0.05), with an average gain indicating a creative category. Novelty: The study demonstrates measurable improvement in multiple indicators of creative thinking—fluency, flexibility, originality, and elaboration—through a friction-force project implemented in a real classroom context. Implications: Findings suggest that integrating project-oriented activities in elementary science instruction can foster active participation, innovation, and problem-solving abilities, supporting the development of higher-order thinking skills in primary education. Highlights: Post-instruction scores were significantly higher than baseline measurements. Learners actively generated diverse ideas while producing tangible science projects. Statistical analysis confirmed meaningful progress across assessed thinking indicators. Keywords: Project Based Learning; Creative Thinking Skills; Elementary Science Education; Pre-Experimental Design; Primary School Students